Studi Pendahuluan Profil Penggunaan Obat dan Kepatuhan terhadap Pengobatan pada Pasien Lupus di Komunitas - Sylvi Irawati; Adji Prayitno; Angel Angel; Rosati Herma Safitri (Fakultas Farmasi Universitas Andalas, 2015)
This study aimed to describe medications used and compliance in systemic lupus erythematosus (SLE) patients. This was a nonexperimental and prospective study. Patients aged ≥18 years old, used medications for SLE and consented to participate were included in this study. Data was collected from September to November 2012 by observation and interview. Pill count method was used to measure patients compliance. All of 15 patients participated in this study were female with median of age 30 years old. Three patients received single medication and the rest received combination drugs. All patients used corticosteroids. In 12 patients it was combined with 1 or 2 of disease-modifying antirheumatic drugs (DMARDs). More than 50% patients did not comply with their medications. Further research is needed to elicit barriers for noncompliance and to produce strategy for improving the medication-taking-related behaviour in SLE patients.